PAZ6 Cells Constitute a Representative Model for Human Brown Pre-Adipocytes - Kazantzis, Melissa; Takahashi, Virginia; Hinkle, Jessica; Kota, Smitha; Zilberfarb, Vladimir; Issad, Tarik; Abdelkarim, Mouaadh; Chouchane, Lotfi; Strosberg, Arthur Donny (Frontiers in Endocrinology, 2012)
Abstract The role of brown adipose tissue (BAT) in human metabolism and its potential as an anti-obesity target organ have recently emerged. Following recent radiological detection of substantial amounts of BAT in adults by several independent research groups, an increasing number of studies are now dedicated to uncover BAT’s genetic, developmental and environmental determinants. In contrast to the murine BAT, human BAT is not present as a prominent depot in a well-defined location. The diffuse distribution of BAT in several areas in the body significantly limits its availability to research. Human brown adipose tissue cells lines are, therefore, critical in broadening the options available to researchers in the field. The human brown adipose tissue cell line PAZ6 was created to address such demand and has been well characterized by several research groups around the world. In the present review, we discuss their findings and propose potential applications of the PAZ6 cells in addressing the relevant questions in the brown adipose tissue field, namely for future use in therapeutic applications.